Stability of Cu-precipitates in Al-Cu alloys - Staab, Torsten E.M.; Folegati, Paola; Wolfertz, Iris; Puska, Martti J. (MDPI AG, 2018)
We present first principle calculations on formation and binding energies for Cu and Zn as solute atoms forming small clusters up to nine atoms in Al-Cu and Al-Zn alloys. We employ a density-functional approach implemented using projector-augmented waves and plane wave expansions. We find that some structures, in which Cu atoms are closely packed on (100)-planes, turn out to be extraordinary stable. We compare the results with existing numerical or experimental data when possible. We find that Cu atoms precipitating in the form of two-dimensional platelets on (100)-planes in the fcc aluminum are more stable than three-dimensional structures consisting of the same number of Cu-atoms. The preference turns out to be opposite for Zn in Al. Both observations are in agreement with experimental observations.
Keywords: Ab initio calculations; Aluminum copper alloys; DFT-LDA; Guinier-Preston zones; Precipitates